Robert Lima, An annotated bibliography of Ramón del Valle-Inclán. University Park, Pennsylvania State University Libraries, 1972; xi + 401 pp. (Bibliografical series, 4). - Schiavo, Leda (El Colegio de México, 1976)
Se reseñó el libro: An annotated bibliography of Ramón del Valle-Inclán.